Strategic management : competitiveness and globalization - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E. (Cincinnati, Ohio : South-Western College, 2001)
This book is about: Strategic management inputs; Strategic actions; ...
Keywords: Management; Strategic planning; Industrial management; Strategic planning